(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Through this article, we will focus on the ethical and educational aspects of Mahmud Khoja Behbudi’s "Oyna" magazine and its articles. Through Behbudi’s "Oyna" magazine, through the articles written by the pioneers of education on the subject of education, we will dwell on the fact that through their articles, those who sacrificed their lives for the development and future of the country instilled in the nation’s consciousness that education is a duty for women and men. We will also learn about information that is not ours.